(3GdeBH aj TQM GdBOGHs - (3GdESaQGjjfj, CHh GdYdGA, aNQ NQGSGf, eMeO Hf CMeO GdHgTJj GdESaQGjjfj, J (B749(3g` (B1348(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdeJhMO HhLhH GdhLhO hGdbOe (B... (3bGd GdeUfa(B: (3GdefI dhGgH GdYbd (B... (3Cbhd(B: (3GdefI eUOQ enqf Ydjg efI Cj eff Ydjg, jbGd(B: (3GdefI cdGe GdUfjYIs
(3BNQgG (B:s
(3BNQgG(B: (3hGjG eG cGf jdRe KHhJ CMO GdedRhejf hjdRe aj KHhJ CMOgeG Hbhd GdeOYj dhLhH JMbb GddGRe YfO JMbb GdedRhe ajdRe KHhJ GdeOYjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 326s
(3cTa GdXfhf, L (B1: 40s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs